2020
DOI: 10.1111/joim.13156
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 retinal microangiopathy as an in vivo biomarker of systemic vascular disease?

Abstract: Importance. COVID-19 is caused by SARS-CoV-2, a betacoronavirus that uses the angiotensin-converting enzyme-related carboxypeptidase (ACE2) receptor to gain entry into cells. ACE2 receptor is widely expressed in multiple organs, including the retina, an extension of the central nervous system. The ACE2 receptor is involved in the diabetic and hypertensive retinopathy. Additionally, coronaviruses cause ocular infections in animals, including retinitis, and optic neuritis. Objective. To assess whether there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
166
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(185 citation statements)
references
References 17 publications
10
166
2
7
Order By: Relevance
“…On Fig. 3 we can see a follow-up composite of the same patient, where although the lesion is no longer visible on the fundus exam we can still spot it on b-scan OCT. Our findings are consistent with other reports that are now been presented [3][4][5]. We do appreciate all the input received.…”
Section: To the Editorsupporting
confidence: 92%
“…On Fig. 3 we can see a follow-up composite of the same patient, where although the lesion is no longer visible on the fundus exam we can still spot it on b-scan OCT. Our findings are consistent with other reports that are now been presented [3][4][5]. We do appreciate all the input received.…”
Section: To the Editorsupporting
confidence: 92%
“…Optical coherence tomography (OCT) is a noninvasive imaging modality used to detect retinal changes that manifest during systemic disease [36]. COVID-positive individuals typically manifest conjunctivitis and ocular surface pathology; however, OCT and retinal fundus imaging have demonstrated the presence of cotton wool spots (CWS) [37]. CWS are retinal nerve fiber layer infarcts that can be visualized as lesions on imaging [38].…”
Section: Retinal Findings Associated With Covid-19mentioning
confidence: 99%
“…It is unclear if the vascular pathology of COVID-19 is due to hypercoagulation, ischemia (in individuals with diabetes), or a direct virus-induced vasculitis. Landecho et al suggest that a fundoscopic exam on admission may help identify individuals who may be more prone to acute vascular disease, because despite all patients being on heparin, 22% of individuals still developed CWS [37]. Similarly, Marinho et al presented a study which included 12 COVID-positive individuals examined by OCT and fundus images at least 10 days after symptom onset.…”
Section: Retinal Findings Associated With Covid-19mentioning
confidence: 99%
“…It was also pointed out that the absence of near-infrared reflectance imaging, OCT angiography abnormalities as well as follow-up scans should be taken into account while interpreting these findings. Furthermore, Virgo and Mohamed presented two patients with paracentral acute middle maculopathy and acute macular neuroretinopathy following SARS-CoV-2 infection [3] and Landecho et al evaluated 27 asymptomatic subjects with previous COVID-19 respiratory tract infection and found that six of them had cotton wool spots [4]. In addition, Insausti-García et al reported a case of papillophlebitis associated with SARS-CoV-2 [5].…”
mentioning
confidence: 99%